2022
DOI: 10.3389/fmicb.2022.1059227
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between the gut microbiota and metabolism during the third trimester of pregnancy

Abstract: The gut microbiota undergoes dynamic changes during pregnancy. The gut microbial and metabolic networks observed in pregnant women have not been systematically analyzed. The primary purpose of this study was to explore the alterations in the gut microbiota and metabolism during late pregnancy and investigate the associations between the gut microbiota and metabolism. A total of thirty healthy pregnant women were followed from 30 to 32 weeks of gestation to full term. Fecal samples were collected for microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…found that the genus Sellimonas may be a marker of intestinal homeostasis, and its abundance gradually increases with the restoration of intestinal barrier function ( 54 , 55 ). Genus Coprococcus , an important member of the phylum Firmicutes , is known for its production of butyric acid ( 56 ). Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that the genus Sellimonas may be a marker of intestinal homeostasis, and its abundance gradually increases with the restoration of intestinal barrier function ( 54 , 55 ). Genus Coprococcus , an important member of the phylum Firmicutes , is known for its production of butyric acid ( 56 ). Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…known for its production of butyric acid(56). Zhou et al proposed that genus Coprococcus2 is a distinguishing gut microbiota in obese PCOS patients…”
mentioning
confidence: 99%
“…On the other hand, 20-hydroxyarachidonic acid and palmitic acid were enriched at the time of full-term pregnancy. Other metabolites like cyclohexylsulfamate, 3,3-dimethylacrylic acid, hydroxyisocaproic acid, and phenylalanylphenylalanine (Phe-Phe) were also identified in fecal samples from Chinese pregnant women ( Liang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%